Replication Stress: A Review of Novel Targets to Enhance Radiosensitivity-From Bench to Clinic - Zhang, Yuewen; Wu, Lei; Wang, Zhao; Wang, Jinpeng; Roychoudhury, Shrabasti; Tomasik, Bartlomiej; Wu, Gang; Wang, Geng; Rao, Xinrui; Zhou, Rui (Frontiers in Oncology, 2022)
DNA replication is a process fundamental in all living organisms in which deregulation, known as replication stress, often leads to genomic instability, a hallmark of cancer. Most malignant tumors sustain persistent proliferation and tolerate replication stress via increasing reliance to the replication stress response. So whilst replication stress induces genomic instability and tumorigenesis, the replication stress response exhibits a unique cancer-specific vulnerability that can be targeted to induce catastrophic cell proliferation. Radiation therapy, most used in cancer treatment, induces a plethora of DNA lesions that affect DNA integrity and, in-turn, DNA replication. Owing to radiation dose limitations for specific organs and tumor tissue resistance, the therapeutic window is narrow. Thus, a means to eliminate or reduce tumor radioresistance is urgently needed. Current research trends have highlighted the potential of combining replication stress regulators with radiation therapy to capitalize on the high replication stress of tumors. Here, we review the current body of evidence regarding the role of replication stress in tumor progression and discuss potential means of enhancing tumor radiosensitivity by targeting the replication stress response. We offer new insights into the possibility of combining radiation therapy with replication stress drugs for clinical use.